Financial Literacy and Resilience Among Students in Southern Malaysian Public Universities - Isa, Khairunesa; Palpanadan, Sarala Thulasi; Mohammd Adkha, Nuraiman Nadzirah (JBS Nexus, 2025)
This study investigates the relationship between financial literacy and financial resilience among students in Malaysian public universities (IPTA). In the context of rising living costs and limited financial resources, financial literacy emerges as a crucial skill for young adults navigating economic challenges. Utilizing data from 107 respondents, the research examines how socio-demographic factors, financial literacy, and economic resources influence financial resilience. The findings indicate that students with higher financial literacy demonstrate better financial resilience, thereby enhancing student well-being. By advocating for the inclusion of financial management education in university curricula, this study supports Sustainable Development Goal 4 (SDG 4), which emphasizes quality education and lifelong learning opportunities. The integration of financial literacy into educational programs not only prepares students for financial challenges but also contributes to their long-term financial stability and overall well-being.